We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
26
1
avatar

How can i arrange this: (x*y)/z=(a*b)/c to this: c=(z*a*b)/(x*y). Can somebody explain how this was done step by step?

 Oct 27, 2019
 #1
avatar
+1

Solve for c:
(x y)/z = (a b)/c

(x y)/z = (a b)/c is equivalent to (a b)/c = (x y)/z:
(a b)/c = (x y)/z

Take the reciprocal of both sides:
c/(a b) = z/(x y)

Multiply both sides by a b:
 
c = (a b z)/(x y)

 Oct 27, 2019

35 Online Users